PENGARUH MODEL POE (PREDICT-OBSERVE-EXPLAIN) TERHADAP HASIL BELAJAR KIMIA PADA KELAS XI MATERI KELARUTAN DAN HASIL KALI KELARUTAN DI SMA NEGERI 4 PASANGKAYU - M., Erni; Napitupulu, Mery; Sakung, Jamaluddin (Universitas Tadulako, 2013)
The type of in this research is the experimental of research with using of model POE (Predict-Observe-Explain) held in to SMAN 4 Pasangkayu XI science of class. The experiment class (XI IPA 2) using POE learning the model cinsists of 21 student and the class of control (XI IPA 1) using of research conventional learning model to consists of 17 students. This research aims to determine the effect learning of a POE model on learning outcomes in chemistry class XI science student of SMAN 4 Pasangkayu. The test was gave before and after the learning twice (pretest and posttest). The observation sheet was used to observe student’s learning of activities. T test was performed after normality test and data homogenity. Based on the data analysis the average for experiment class is 11.07 with the mastery percentage of 71.42% while of 28.57% did not completed. For a control class average to valve 9,08 with the percentage completeness to valve learning a student 41.17% while not completed of 58.82%. In this matter to pointed that there are to affect of POE model on learning result in chemistry to XI exact science of class with material on the solubility and product solubility to SMAN 4 of Pasangkayu, cause can to interest layer and result of student learning.